The Influence of Naqshbandi Thariqah Wirid Practice on the Development of Students’ Learning Character and Cognitive Skills - Facxy, Razif Artnesa; Firmansyah, Mokh. Iman; Nugraha, Risris Hari (STAI Serdang Lubuk Pakam, 2025)
The decline in student motivation and discipline in learning after the Covid-19 pandemic has become one of the major challenges in Islamic boarding school-based educational institutions. Many students have difficulty concentrating and maintaining their enthusiasm for learning. In this context, this study aims to examine the influence of the habit of reciting the Thariqah Naqsyabandiyah wirid on the formation of learning character among students at the Al-Quran Al-Falah Islamic Boarding School Foundation in West Java. A quantitative correlational method was used, involving 39 final-year students. Data was collected through questionnaires measuring the frequency of wirid and learning characteristics, then analyzed using descriptive statistics and Pearson's correlation test. The results of the study indicate a significant positive correlation between the practice of wirid and improvements in learning characteristics, including religiosity, discipline, honesty, hard work, and humility. Additionally, wirid provides a calming effect that enhances focus and mental readiness. These findings emphasize the importance of spiritual routines in supporting character development. Implications suggest that educational institutions can integrate wirid practices as a strategy for character formation and mental strengthening among students, particularly to address the negative impacts of the post-pandemic period on learning quality.